2000
DOI: 10.1016/s0399-1784(00)01117-8
|View full text |Cite
|
Sign up to set email alerts
|

Fish fauna of a mixed meadow composed by the seagrasses Cymodocea nodosa and Zostera noltii in the Western Mediterranean

Abstract: The fish fauna of a shallow meadow composed by the seagrasses Cymodocea nodosa and Zostera noltii was studied in the Gulf of Olbia (NE Sardinia, Italy; Western Mediterranean). Visual censuses were conducted monthly from August 1995 to August 1996. Environmental variables for water temperature, salinity and seagrass shoot density were collected on each sampling occasion. A total of 23 fish species from eight families were recorded. Planktivorous species (Atherinids) numerically dominated the fish community, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 35 publications
(49 reference statements)
8
32
0
Order By: Relevance
“…In terms of habitat preferences, investigated using the juvenile density as a proxy, Spondilyosoma cantharus and Diplodus annularis were mostly associated to marine phanerogams (especially small-sized seagrasses) for settlement. Similar results for these two species were reported from other Western Mediterranean locations (Francour & Le Direach 1994;Harmelin-Vivien et al 1995;Biagi et al 1997;Guidetti & Bussotti 1997;Tunesi et al 1997;Guidetti 2000;Guidetti & Bussotti 2000). This shows their strict association with marine phanerogams, even though it is long been known that they can use additional/alternative vegetated habitats (e.g.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In terms of habitat preferences, investigated using the juvenile density as a proxy, Spondilyosoma cantharus and Diplodus annularis were mostly associated to marine phanerogams (especially small-sized seagrasses) for settlement. Similar results for these two species were reported from other Western Mediterranean locations (Francour & Le Direach 1994;Harmelin-Vivien et al 1995;Biagi et al 1997;Guidetti & Bussotti 1997;Tunesi et al 1997;Guidetti 2000;Guidetti & Bussotti 2000). This shows their strict association with marine phanerogams, even though it is long been known that they can use additional/alternative vegetated habitats (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…Mullus surmuletus chiefly used sublittoral sandy habitats in SE Italy. Other authors found similar patterns, but also reported that juveniles of this species can be found associated with marine phanerogams (Garcia-Rubies & Macpherson 1995;Guidetti & Bussotti 2000) or can be collected in open waters far from the coast (Deudero 2002). Juveniles of Chromis chromis were always found to be chiefly associated with sublittoral rocks composed by blocks and boulders.…”
Section: Discussionsupporting
confidence: 57%
“…The faunistic communities of Posidonia oceanica have been thoroughly studied over the last decades (Russo et al 1984a, b;Templado 1984;Gambi et al 1992;Sánchez-Jerez et al 1999;Francour 1997), and the same applies to the communities associated with Zostera marina (Jacobs and Huisman 1982;Jacobs et al 1983;Currás et al 1993;Mattila et al 1999;2009a, b;. In contrast, the fauna of C. nodosa beds have scarcely been studied (García-Raso et al 2006;Barberá et al 2001;Guidetti and Bussotti 2000;Sánchez-Jerez et al 1999;Ledoyer 1966;Sfriso et al 2001;Brito et al 2005), especially with regard to the temporal patterns of molluscan assemblages (Chemello et al 1997;Terlizzi and Russo 1997;Tuya et al 2001). In addition to seasonal changes, there is a diel variability related to short-term movements of the animals during the day-night cycle along the seagrass shoots or from adjacent habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Although the abundant presence of Atherinidae species (e.g. Atherina boyeri and A. presbyter) in south European estuaries and coastal areas (Atlantic and Mediterranean) is well known (Labourg et al 1985, Bouchereau et al 2000, Guidetti & Bessotti 2000, the abundant presence of YOY from Atherinidae family in intertidal areas of European saltmarshes is not well documented. However, in shallow littoral zones along the U.S. coast, species of the Atherinidae family (e.g.…”
Section: Habitat Differencesmentioning
confidence: 99%